2003
DOI: 10.3748/wjg.v9.i3.612
|View full text |Cite
|
Sign up to set email alerts
|

Endosonography with linear array instead of endoscopic retrograde cholangiography as the diagnostic tool in patients with moderate suspicion of common bile duct stones

Abstract: Vast majority of patients with moderate suspicion of CBDS and no stones on EUS with linear array can avoid invasive evaluation of biliary tree with ERC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…Furthermore, it has been previously reported [17] that a considerable portion of patients with intermediate risk of CBD stones (as in our current study consisting of a group of patients with no direct evidence of CBD stone found by transabdominal ultrasound/CT scan) have no evidence of stones by linear EUS, thus, avoiding unnecessary invasive evaluation of the bile duct with ERCP.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, it has been previously reported [17] that a considerable portion of patients with intermediate risk of CBD stones (as in our current study consisting of a group of patients with no direct evidence of CBD stone found by transabdominal ultrasound/CT scan) have no evidence of stones by linear EUS, thus, avoiding unnecessary invasive evaluation of the bile duct with ERCP.…”
Section: Discussionmentioning
confidence: 54%
“…Gallstones can be documented within the common bile duct with accuracy similar to ERCP by EUS (39,205,(207)(208)(209)(210)(211)(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226), with somewhat lower accuracy by MRCP (227)(228)(229)(230)(231)(232)(233), and by intraoperative cholangiography at the time of laparoscopic cholecystectomy (234)(235)(236)(237). Identification of a biliary etiology of acute pancreatitis is important because recurrent episodes will occur in one-third to two-thirds of these patients in follow-up periods of as short as 3 months unless gallstones are eliminated (238,239).…”
Section: Treatment Guideline Vii: Role Of Ercp and Biliary Sphincteromentioning
confidence: 99%
“…Kohut et al did not use ERCP either, but their clinical follow-up for negative CBDS on linear EUS was of longer duration. 10 The limitation of our study is the shorter follow-up period in some cases of negative CBDS, although the median follow-up duration was 9 months.…”
Section: Discussionmentioning
confidence: 93%